2018
DOI: 10.3390/biom8040165
|View full text |Cite
|
Sign up to set email alerts
|

RNA Sequencing Provides Insights into the Regulation of Solanesol Biosynthesis in Nicotiana tabacum Induced by Moderately High Temperature

Abstract: Solanesol is a terpene alcohol composed of nine isoprene units that mainly accumulates in solanaceous plants, especially tobacco (Nicotiana tabacum). The present study aimed to investigate the regulation of solanesol accumulation in tobacco leaves induced by moderately high temperature (MHT). Exposure to MHT resulted in a significant increase in solanesol content, dry weight, and net photosynthetic rate in tobacco leaves. In MHT-exposed tobacco leaves, 492 and 1440 genes were significantly up- and downregulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…Tobacco leaves have a variety of chemical components, many of which are bioactive [1,2,3]. Cembranoids are macrocyclic diterpenes comprising four isoprene units bonded head-to-tail, and are natural products with a parent skeleton consisting of a 14-membered ring, three symmetrically distributed methyl groups and one isopropyl group; the cembranoid parent nucleus has a symmetry plane with an axis passing through C-1 and C-8 [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Tobacco leaves have a variety of chemical components, many of which are bioactive [1,2,3]. Cembranoids are macrocyclic diterpenes comprising four isoprene units bonded head-to-tail, and are natural products with a parent skeleton consisting of a 14-membered ring, three symmetrically distributed methyl groups and one isopropyl group; the cembranoid parent nucleus has a symmetry plane with an axis passing through C-1 and C-8 [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Solanesol plays a key role in the response of tobacco to biotic stresses caused by the TMV or Pseudomonas syringae pv. tabaci [31] and environmental factors such as moderately high temperature [4]. In a previous study, it was found that upon TMV or P. syringae pv.…”
Section: Factors Associated With Solanesol Accumulation In Plantsmentioning
confidence: 99%
“…Solanesol, an aliphatic terpene alcohol composed of nine isoprene units, is mainly found in Solanaceae plants such as tobacco ( Nicotiana tabacum ), tomato ( Solanum lycopersicum ), and potato ( Solanum tuberosum ) [1,2,3,4,5]. As the chemical synthesis of solanesol is difficult due to its long carbon chains [6], solanesol is mainly obtained through extraction from solanaceous plants [1,2,3,4,7]. To the best of our knowledge, tobacco is the richest plant source of solanesol; among the various organs of tobacco plants, leaves possess the highest content of solanesol, followed by stems and roots [1,2,8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations